Measuring peri-implant bone lesions using low-dose cone-beam computed tomography - Horsch, Laura; Tasaka, Akinori; Trebing, Charlotte Theresa; Hilgenfeld, Tim; Kosinski, Matthias; Kronsteiner, Dorothea; Rammelsberg, Peter; Schwindling, Franz Sebastian (Journal of prosthodontic research, 2022)
Purpose: High-definition cone-beam computed tomography (HD-CBCT) offers superior image quality at the cost of higher radiation dose compared to low-dose CBCT (LD-CBCT). The aim of this study was to investigate whether peri-implant bone lesions can be accurately quantified using LD-CBCT, even when including the influence of surrounding tissues.Methods: Twelve titanium implants restored with all-ceramic crowns were placed in bovine bone, and peri-implant lesions were prepared. Radiographic imaging was performed using IR (intraoral radiography), HD-CBCT and LD-CBCT. To simulate the in-vivo situation, the samples were placed inside a dry human mandible, and a second LD-CBCT imaging was performed (LD-CBCT*). The datasets were presented to four observers in random order. Maximum lesion depth and width were measured in a standardized mesiodistal slice in IR, HD-CBCT, LD-CBCT, and LD-CBCT*. Mean lesion depth and width measurements for each sample in HD-CBCT served as reference.Results: Interrater agreement was slight for depth and excellent for width in HD-CBCT and both LD modes. For all observers, measurement deviations from HD-CBCT were below 0.3 mm in the LD protocols (LD-CBCT depth: 0.22 ± 0.17 mm, width: 0.22 ± 0.13 mm; LD-CBCT* depth: 0.24 ± 0.23 mm, width: 0.25 ± 0.21 mm) and at 0.4 mm in IR.Conclusion: Absolute differences between LD-CBCT and HD-CBCT are small, although surrounding tissues decrease LD-CBCT image quality. Within the limitations of an in-vitro trial, LD-CBCT may become an adequate imaging modality for monitoring peri-implant lesions at a substantially decreased radiation dose.
Advance online publication: July 21, 2021
Gesehen am 05.01.2023